The role of epicardial adipose tissue dysfunction in cardiovascular diseases: an overview of pathophysiology, evaluation, and management - Li, Cheng; Liu, Xinyu; Adhikari, Binay Kumar; Chen, Liping; Liu, Wenyun; Wang, Yonggang; Zhang, Huimao (Frontiers in Endocrinology, 2023)
In recent decades, epicardial adipose tissue (EAT) has been at the forefront of scientific research because of its diverse role in the pathogenesis of cardiovascular diseases (CVDs). EAT lies between the myocardium and the visceral pericardium. And, the same microcirculation exists both in epicardial fat and myocardium. Under physiological circumstances, EAT serves as cushion and protects coronary arteries and myocardium from violent distortion and impact. Besides, EAT acts as an energy lipid source, thermoregulator and endocrine organ. Under pathological conditions, EAT dysfunction promotes various CVDs progression in several ways. It seems that various secretions of the epicardial fat are responsible for myocardial metabolic disturbances, and finally leads to CVDs. Therefore, EAT might be an early predictor of CVDs. Furthermore, different noninvasive imaging techniques have been proposed to identify and assess EAT as an important parameter to stratify the CVDs risk. We also present the potential therapeutic possibilities aiming at modifying the function of EAT. This paper aims to overview the potential role of EAT in CVDs, discuss different imaging techniques to assess EAT, and provided potential therapeutic options for EAT. Hence, EAT may represent as a potential predictor and a novel therapeutic target for management of CVDs in future.